17.87% Efficiency All‐Polymer Tandem Solar Cell Enabled by Complementary Absorbing Polymer Acceptors. (27th November 2022) - Ma, Qing; Jia, Zhenrong; Meng, Lei; Yang, Hang; Zhang, Jinyuan; Lai, Wenbin; Guo, Jing; Jiang, Xin; Cui, Chaohua; Li, Yongfang
Abstract: All‐polymer solar cells (all‐PSCs) possess distinguished advantages of excellent morphology stability, thermal stability, and mechanical flexibility. Tandem solar cells, by stacking two sub‐cells, can absorb more photons in a wider wavelength range and can reduce thermal losses. However, limitation of polymer acceptors with suitable bandgaps hinders the development of tandem all‐PSCs. Herein, highly efficient tandem all‐PSCs are fabricated by employing two polymerized small molecular acceptors (PSMAs) of wide bandgap PIDT (1.66 eV) in the front cell and narrow bandgap PY‐IT (1.4 eV) in the rear cell. The two sub‐cells with the polymer donors of PM7 in front cell and PM6 in rear cell show high open circuit voltage ( V oc ) of 1.10 V for the front cell and 0.94 V for the rear cell. By rational device optimizations, the best power conversion efficiency of 17.87% is achieved for the tandem all‐PSCs with high V oc of 2.00 V. 17.87% is one of the highest efficiency for the all‐PSCs, and 2.00 V is one of the highest V oc for all the tandem organic solar cells. Moreover, the tandem all‐PSCs show excellent thermal and light‐soaking stability compared with their small‐molecule counterparts. The results provide insight to the potential of bandgap tuning in PSMAs, and indicate that the tandem architecture is an effective strategy to boost performance of the all‐PSCs. Abstract : High performance tandem all‐polymer solar cells are fabricated by employing two complementary absorbing polymerized small molecule acceptors (PSMAs), a wide‐band gap PSMA PIDT in front cell with PM7 as polymer donor and a narrow‐bandgap PSMA PY‐IT in rear cell with PM6 as polymer donor. The optimized device demonstrates a high power conversion efficiency of 17.87% with V oc reaching 2.00 V.